Gamma-ray bursts with MeerLICHT - De Wet, Simon (Department of Astronomy, 2025)
The subject of this thesis is the multi-wavelength observational study of gamma-ray burst (GRB) afterglows. The driving force behind this work is the fully robotic MeerLICHT optical telescope which is able to rapidly slew to the position of a GRB in the sky and obtain multi-lter follow-up observations of the early phases of the afterglow, when non-standard behaviour may occur. Following the introduction, the thesis consists of four main chapters: a chapter outlining the more than two year GRB follow-up programme undertaken with MeerLICHT in which we followed-up 29 bursts, and three chapters presenting detailed studies on individual GRBs. The rst of these studies focuses on GRB 210731A. Starting 286 seconds post-trigger, MeerLICHT obtained a highly unusual light curve consisting of three peaks, which we interpreted as being due to energy injection. Through multi-wavelength theoretical modeling we found that a forward shock model within a stellar wind medium could explain all of our X-ray, optical and radio data, but not our 1.4 GHz upper limits. We suggested that a possible thermal electron population might explain the additional opacity at lower radio frequencies. The subject of the second detailed study is GRB 220627A, a rare burst consisting of two gamma-ray emission episodes separated by almost 1000 s. The discovery of the optical afterglow by MeerLICHT led to spectroscopic observations which secured the burst redshift to z=3.08, making this the most distant ultra-long GRB to date. Our modelling and afterglow analysis showed that GRB 220627A does not appear to have a dierent progenitor compared to the wider long GRB propulation. The third detailed study encompasses GRB 210702A. This burst was unique for being the rst GRB with a clear rebrightening in its millimeter light curve which we attempted to explain via energy injection or a reverse shock from a late-time shell collision. Prior to the millimeter rebrightening, we found that the X-ray, optical and millimeter data could be reconciled within a standard forward shock model in a stellar wind medium, however, similar to other bursts with extensive radio data sets, no standard model could explain all of our radio data.